Russian and Indian preschool educators’ beliefs about play activities: a comprehensive study - Veraksa, Aleksander; Chursina, Apollinaria; Singh, Purnima; Ramakrishna, Madhumita; Jain, Nishtha (Frontiers in Education, 2023)
In this study, preschool teachers’ beliefs regarding play in preschool children in its various forms (role-play, rough-and-tumble play, digital play), and the process of its development in groups of children based on samples of Russian and Indian educators were examined. From Russia, 3,013 respondents (all women), aged 18–77 (M = 41.57; SD = 10.02) took part in the study, and 116 respondents (10.34% men), aged 23–50 (M = 36; SD = 9) from India also participated. An original questionnaire aimed at assessing attitudes toward different types of play in preschool educators was used. This instrument consisted of various sections which focused on the understanding of play and its place in the everyday routine of the child group, role-play patterns characteristics (i.e., preferred plots, play materials, course of the play), rough-and-tumble play practice, attitudes toward digital play, and educators’ play competence (self-assessment regarding difficulties with joining the play, suggesting a plot or materials for play, etc.). Our main finding was that although the vast majority of educators in both cultures recognize the value of play for child development, this belief does not find practical expression in the daily life of the child group. Our data showed that Indian educators are more likely to be mediators of children’s experience in play, while their Russian counterparts are more likely to be engaged in the role-play with the children. The content characteristics of play among children in Russia and India were also described. There are differences in attitudes toward digital play: more experienced teachers have a more positive attitude toward the activities of children with digital devices, they see opportunities for the development of a child in digital play. At the same time, teachers in whose groups children enter into digital play not only have a positive attitude toward this type of play but also evaluate themselves more positively in the process of playing with children.